2014
DOI: 10.18632/oncotarget.2768
|View full text |Cite
|
Sign up to set email alerts
|

Targeting ornithine decarboxylase reverses the LIN28/Let-7 axis and inhibits glycolytic metabolism in neuroblastoma

Abstract: LIN28 has emerged as an oncogenic driver in a number of cancers, including neuroblastoma (NB). Overexpression of LIN28 correlates with poor outcome in NB, therefore drugs that impact the LIN28/Let-7 pathway could be beneficial in treating NB patients. The LIN28/Let-7 pathway affects many cellular processes including the regulation of cancer stem cells and glycolytic metabolism. Polyamines, regulated by ornithine decarboxylase (ODC) modulate eIF-5A which is a direct regulator of the LIN28/Let-7 axis. We propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 34 publications
3
41
0
Order By: Relevance
“…Combination drug therapies offered several advantages such as better efficacy, Interestingly, sensitivities of NB cells to DFMO and bortezomib were correlated with LIN28B transcript levels. Previously, we reported that BE(2)-C cells expressed high levels of LIN28B and MYCN whereas SMS-KCNR cells expressed high MYCN but low LIN28B transcripts [25]. We observed that combination therapy of DFMO and bortezomib produced higher synergistic effect in BE(2)-C cells as compared to SMS-KCNR cells, which correlated with their LIN28 expression levels.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Combination drug therapies offered several advantages such as better efficacy, Interestingly, sensitivities of NB cells to DFMO and bortezomib were correlated with LIN28B transcript levels. Previously, we reported that BE(2)-C cells expressed high levels of LIN28B and MYCN whereas SMS-KCNR cells expressed high MYCN but low LIN28B transcripts [25]. We observed that combination therapy of DFMO and bortezomib produced higher synergistic effect in BE(2)-C cells as compared to SMS-KCNR cells, which correlated with their LIN28 expression levels.…”
Section: Discussionsupporting
confidence: 52%
“…These results also suggest that although DFMO and bortezomib act on different targets, they may mediate their actions, at least partly, through a common mechanism involving LIN28. DFMO works by irreversibly binding to and inhibiting ODC, the rate limiting enzyme in polyamine biosynthesis and the upstream regulator of LIN28 expression [25] [40]. Polyamines are also shown to regulate NF-kB pathway [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeting LIN28B is currently under extensive investigation in a variety of cancers, with promising results in neuroblastoma and pediatric brain tumors. 36,37 It thus will be of great interest to evaluate whether treatment with LIN28B-targeting agents can enhance survival rates in this novel fetal-like subgroup of JMML.…”
Section: Lin28b Defines a Fetal-like Stem Cell Signature In Jmml Patimentioning
confidence: 99%
“…In vitro and xenograft models have demonstrated decreased neurosphere and tumor formation as a result of decreased LIN28 and increased Let7 after DFMO treatment. 17,18 DFMO has been clinically studied through the Beat Childhood Patients with HRNB who completed standard upfront therapy without progression were eligible for enrollment. DFMO was initiated within 120 days of the completion of therapy at a dose of 750 ± 250 mg/m 2 /dose, twice daily.…”
mentioning
confidence: 99%